Effectiveness of Health Coaching Interventions in Improving Tuberculosis Treatment Adherence: A Systematic Review - Agnes Ephipania Dua Bura; Retno Indarwati; Eka Mishbahatul Mar'ah Has (GLOBAL HEALTH SCIENCE GROUP, 2026)
Tuberculosis (TB) is still a global health challenge, especially related to low patient adherence to treatment. This non-adherence can lead to drug resistance, recurrence, and the wider spread of the disease. Health coaching interventions, especially those based on psychosocial approaches such as the GROW model, have developed as a potential strategy in improving health behaviors. The purpose of this review was to evaluate the effectiveness of health coaching interventions on the medication adherence of TB patients. This systematic review was conducted on seven quantitative articles (RCTs and quasi-experiments) focusing on health coaching interventions in TB patients, with or without telenursing support. The literature was selected based on inclusion criteria including adult TB patients, health coaching interventions, and measurement of compliance outcomes. Data were extracted narratively based on design, sample size, location, instruments, key outcomes, and nurse roles. Most studies showed that health coaching interventions significantly improved medication adherence (with a p-value < 0.05). The GROW model is the most commonly used approach. The intervention was carried out face-to-face and dominated by the active role of the nurse as a coach. Although there was variation in duration and frequency, interventions over 4-8 weeks showed a positive impact. Health coaching is effective in improving TB treatment adherence. The role of nurses as coaches has proven to be crucial in the process of changing patient behavior.